Violations of independence: ethnicity and COVID-19 in Brazil (2020)
Pedro Baqui and colleagues (August 2020) 1 did a cross-sectional observ - ational study of hospital mortality from COVID-19 in Brazil to assess variations in mortality according to ethnicity and region, adjusting for many clinical features. The study revealed the presence of societal inequities in the effects of COVID-19: mortality was significantly higher in Pardo (mixed ethnicity) and Black Brazilians than in White Brazilians (hazard ratio [HR] 1·45, 95% CI 1·33–1·58 for Pardo Brazilians; 1·32, 1·15–1·52 for Black Brazilians).